Bidens pilosa extract and sub-fractions induce adipogenesis and exert glucose uptake in 3T3-L1 adipocytes - Tolo, M. M. (My University, 2020)
Diabetes mellitus has become a global epidemic, particularly type 2 diabetes. Obesity is one of the causes of type 2 diabetes mellitus due to its link with induced insulin resistance. There is no cure for diabetes mellitus and, as such, it is managed by using standard drugs which have side effects, and can be toxic, expensive and unavailable. People have resorted to the use of medicinal plants to treat diabetes and its complications. The aim of this study was to test the anti-obesity and anti diabetic properties of Bidens pilosa crude extract and its sub-fractions using C2C12 myoblasts and 3T3-L1 adipocytes. The crude extract and the most active sub fractions were selected for further analysis because of their ability to stimulate glucose uptake and induction of adipogenesis. Bidens pilosa leaves were selected for this current study. They were firstly extracted using absolute methanol and further subjected to solvent-solvent fractionation to obtain the n-butanol, ethyl acetate, water, hexane, chloroform and 35% water in methanol sub-fractions. Qualitative phytochemical analysis was performed using thin layer chromatography (TLC) and standard chemical tests. Total phenolic and flavonoid content were determined quantitatively using a calorimetric method with Folin-Ciocalteu’s reagent. For their antidiabetic potential, the extracts were evaluated chromogenically and calorimetrically for antiglycation and α-amylase inhibitory activity. The cytotoxicity of the extracts on 3T3-L1 preadipocytes and C2C12 myotubes were determined using the MTT assay. The adipogenesis inducing effect of the extract was tested using the adipogenesis kit. More compounds were found on chromatograms eluted in EMW mobile phase (Ethyl acetate: methanol: water). The extracts were shown to contain a variety of secondary metabolites, and high phenolic and flavonoids contents. Crude, chloroform, n butanol and water sub-fractions had high antioxidant activity. Alpha amylase activity was highly inhibited in the crude extract and all sub-fractions, with the highest inhibitory activity observed in the crude extract and the chloroform, n-butanol and water Sub-fractions (IC50 1.25 ± 2.5 mg/ml). The cytotoxic profiles indicated that all extracts are non-cytotoxic at concentrations of 15.63 µg/ml. Extracts at a concentration of 31.25 µg/ml were shown to stimulate the accumulation of triglycerides using 3T3-L1 adipocytes. The extracts also exhibited significant (P < 0.05) glucose uptake activity. In conclusion, Bidens pilosa contains constituents that inhibit α-amylase, antiglycation formation and modulates uptake of glucose in 3T3-L1 adipocytes. The use of B. pilosa in combination with insulin revealed the synergistic effects in facilitating glucose uptake in both C2C12 myotubes and 3T3- L1 adipocytes. This suggests that there might be some binding compounds found in the plant extracts that are responsible for the stimulation of expression of several genes that encode for proteins involved in the metabolism of glucose. However, the use of B. pilosa, in combination with metformin, results in a decreased glucose uptake. Bidens pilosa have the fast-acting insulin mimetic properties. Furthermore, the plant was shown to stimulate the accumulation of triglycerides in 3T3-L1 adipocytes, signifying the plant can induce adipogenesis at 30µg/ml
Thesis (M. Sc.(Biochemistry)) -- University of Limpopo, 2020
Keywords: Diabetes mellitus; Type 2 diabetes; Obesity; Insulin resistance; Diabetes; Diabetic mellitus; Obesity; Insulin resistance